Lifecycle Exchange for Asset Data (LEAD): A proposed process model for managing asset dataflow between building stakeholders using BIM open standards. Issue 5 (4th November 2019) - Alnaggar, Ahmed; Pitt, Michael
Abstract : Purpose: The purpose of this study is to outline the problems associated with asset information management using the Construction Operations Building Information Exchange (COBie) standard and to analyse the causes of industry failure to successfully adopt the standard. Based on this analysis, the paper will propose a process model, namely, Lifecycle Exchange of Asset Data (LEAD) to manage asset dataflow between all building stakeholders from design to construction and ultimately to the facility management team. This model aims to help the construction supply chain to produce complete and high-quality asset data that supports the operation phase of the built environment. Design/methodology/approach: A review of relevant studies provided a theoretical background for this study. The authors then collected and analysed COBie data from five live construction projects using building information modelling (BIM) projects from different design and construction companies. The process model is based on an industry placement within Bouygues UK construction company, which was a Tier 1 building contractor in London in the period from December 2016 to December 2018. The researcher used an inductive approach observing current practises in two construction projects to produce "LEAD" model. Then a focus group was conducted with industry experts to discuss and refine the process model. Findings: Analysis of literature and data collected in the course of this study revealed that although COBie is a BIM Level 2 standard in the UK, there is currently a low success rate in producing complete and accurate COBie data in the UK construction industry. This low rate is because of COBie's rigid data syntax/structure, complexity and ambiguity of its data exchange process, which suggests that COBie may not be the future of the industry. Based on these findings, the study proposed a process model, namely, "LEAD, " to improve COBie output and also to be used with project-specific information requirements. Practical implications: To the best of the authors' knowledge, this paper is one of the first to focus solely on asset data exchange process using COBie standard and highlights the problems the industry faces in this remit. The study is based on industry placement for two years, so the analysis is based on actual and current industry problems. Current industry practices also informed the "LEAD" model, and the model provides a step-by-step guidance in producing and exchanging BIM asset data in all stages of the building lifecycle. Originality/value: This paper provides a detailed analysis of the most common problems associated with COBie as an asset data exchange standard. Understanding these problems is of high value for industry practitioners to avoid them in projects. The paper also proposed a novel process model that can be used either to improve COBie quality or can be used with any project-specific data requirements.